Perlindungan Hukum Sinematografi Terhadap Pengaksesan Tanpa Hak Oleh Pengguna Aplikasi Telegram Berdasarkan Undang-Undang Hak Cipta Dan Undang-Undang Informasi Dan Transaksi Elektronik Di Indonesia - Kemala Megahayati; Muhamad Amirulloh; Helitha Novianty Muchtar (Universitas Serang Raya, 2021)
Film as a cinematographic work is an object protected by copyright. Film and ICT are rapidly growing in Indonesia. Along with this, digital piracy occurs very often. This happens in instant messaging application, Telegram. Public channel is an available feature on Telegram that misused by its users to spread films illegally. This research was conducted to determine regulations about accessing cinematography on Telegram and Telegram Messenger Inc. liability concerns accessing cinematography by its users. The method is juridical normative by examining secondary data from primary, secondary, and tertiary legal materials obtained through literature study related to copyright and over-the-top services. The results show that accessing cinematography on Telegram violates economic rights according to Article 9 (1) b Copyright Law which is categorized as piracy in accordance with Article 113 (4) Copyright Law and Telegram Messenger Inc. as application organizer should be responsible secondarily for piracy in a civil lawsuit according to Article 99 Copyright Law and Article 38 ITE Law, administrative and criminal that occurs due to negligence in monitoring the activities of its users. Then, primary liability can be requested to application users who do not obey the terms of services of the telegram application which has an exoneration clause as a way to prevent copyright infringement in telegram application.